The Extracellular, Cellular, and Nuclear Stiffness, a Trinity in the Cancer Resistome—A Review - Deville, Sara Sofia; Cordes, Nils (Frontiers in Oncology, 2019)
Alterations in mechano-physiological properties of a tissue instigate cancer burdens in parallel to common genetic and epigenetic alterations. The chronological and mechanistic interrelation between the various extra- and intracellular aspects remains largely elusive. Mechano-physiologically, integrins and other cell adhesion molecules present the main mediators for transferring and distributing forces between extracellular matrix (ECM), via focal adhesomes to cytoskeleton and nucleus and vice versa of the single cell thereby affecting the pathophysiology of multicellular cancer tissues. In combina-tion with simultaneous activation of diverse downstream signaling pathways, the phenotypes of can-cer cells are created and driven characterized by deregulated transcriptional and biochemical cues that elicit the hallmarks of cancer. It, however, remains unclear how elasto-static modifications, i.e. stiffness, in the extracellular, intracellular and nuclear compartment contribute and control the re-sistance of cancer cells to therapy. In this review, we discuss how stiffness of unique tumor compo-nents dictates therapy response and what is known about the underlying molecular mechanisms.